Efficacy and safety of immune checkpoint inhibitors combined with chemotherapy as first-line treatment for extensive-stage small cell lung cancer: a meta-analysis based on mixed-effect models - Zheng, Jianqing; Deng, Yujie; Huang, Bifen; Chen, Xiaohui (Frontiers in Medicine, 2023)
Background Extensive-stage small cell lung cancer (ES-SCLC) is a highly invasive and fatal disease with limited therapeutic options and poor prognosis. Our study aims to systematically evaluate the efficacy and safety of immune checkpoint inhibitors combined with chemotherapy (ICIs+ChT) vs. chemotherapy alone (ChT) in the first-line treatment of ES-SCLC. Methods A literature search was performed for randomized controlled trials (RCTs) related to “ICIs+ChT” vs. “ChT” in the first-line treatment of ES-SCLC in PubMed, Cochrane Library, Embase, CNKI, and other databases. RevMan 5.4 software was used to perform meta-analyses with hazard ratio (HR) and relative risk (RR). SAS 9.4 software was applied to conduct a mixed-effect model meta-analysis of the survival outcomes and draw survival curves. Results A total of 2,638 patients with ES-SCLC from 6 RCTs were included, of which 1,341 patients received “ICIs+ChT” and 1,297 received ChT. Based on the meta-analysis results provided by the mixed-effect model, patients receiving the “ICIs+ChT” regimen had a significantly longer overall survival (OS, HR = 0.800, 95% CI = 0.731–0.876, P < 0.001) and progression-free survival (PFS, HR = 0.815, 95% CI = 0.757–0.878, P <0.001) in comparison to those receiving ChT only. Compared with ChT, “ICIs+ChT” did neither improve the objective response rate (ORR, RR = 1.06, 95% CI = 1.00–1.12, P = 0.06) nor did it improve the disease control rate (DCR, RR = 0.97, 95% CI = 0.92–1.03, P = 0.35). Although the incidence of grade 3 to 5 treatment-related adverse events (trAEs) in the “ICIs+ChT” subgroup did not increase (RR = 1.16, 95% CI = 0.97–1.39, P = 0.11), the incidence of grade 3 to 5 immune-related adverse events (irAEs) increased significantly (RR = 4.29, 95% CI = 1.73–10.61, P < 0.00001). Conclusion ICIs+ChT regimen could significantly prolong OS and PFS in patients with ES-SCLC compared with ChT alone. Although the incidence of irAEs in “ICIs+ChT” is higher than that in the “ChT” subgroup, the incidence of trAEs is similar within the two subgroups. ICIs combined with chemotherapy demonstrated a good choice as first-line treatment for ES-SCLC. Systematic review registration PROSPERO, identifier: CRD42022348496.